Dengue Virus Infection Causes the Activation of Distinct NF-κB Pathways for Inducible Nitric Oxide Synthase and TNF-α Expression in RAW264.7 Cells - Yi-Lin Cheng; Yee-Shin Lin; Chia-Ling Chen; Shu-Wen Wan; Yi-Dan Ou; Chia-Yi Yu; Tsung-Ting Tsai; Po-Chun Tseng; Chiou-Feng Lin (Mediators of Inflammation)
Infection with dengue virus (DENV) causes an increase in proinflammatory responses, such as nitric oxide (NO) generation and TNF-α expression; however, the molecular mechanism underlying this inflammatory activation remains undefined, although the activation of the transcription factor NF-κB is generally involved. In addition to TNF-α production in DENV-infected murine macrophage RAW264.7 cells, inducible NO synthase was transcriptionally and posttranslationally elevated and accompanied by NO generation. NF-κB is known to be activated by DENV infection. Pharmacologically inhibiting NF-κB activation abolishes iNOS/NO biosynthesis and TNF-α production. With inhibition, the potential role of NF-κB in oxidative signaling regulation was prevented during DENV infection. Heat-inactivated DENV failed to cause the identified inflammatory responses. Pharmacological inhibition of TLR3 partly decreased NF-κB activation; however, it effectively abolished inducible iNOS/NO biosynthesis but did not inhibit TNF-α production. In contrast to TLR3, viral protein NS2B3 also independently contributed to NF-κB activation to regulate TNF-α production. These results show the distinct pathways for NF-κB activation caused by DENV infection individually for the regulation of iNOS/NO and TNF-α expression.